A Variational Approach to Scripts - Albarracin, Mahault; Constant, Axel; Friston, Karl J.; Ramstead, Maxwell James D. (Frontiers in Psychology, 2021)
This paper proposes a formal reconstruction of the script construct by leveraging the active inference framework, a behavioural modelling framework that casts action, perception, emotions, and attention as processes of (Bayesian or variational) inference. We propose a first principles account of the script construct that integrates its different uses in the behavioural and social sciences. We begin by reviewing the recent literature that uses the script construct. We then examine the main mathematical and computational features of active inference. Finally, we leverage the resources of active inference to offer a formal model of scripts. Our integrative model accounts for the dual nature of scripts (as internal, psychological schema used by agents to make sense of event types and as constitutive behavioural categories that make up the social order) and also for the stronger and weaker conceptions of the construct (which do and do not relate to explicit action sequences, respectively).